The Technical Mediator in Arab Theater: Their Tools and Skills (Al-Academy, 2023)
The artistic mediation in theater connects the human elements with the material elements in the theatrical production process. The human artistic mediator plays a crucial role in achieving the artistic and expressive goals of the theatrical work, requiring high skills and expertise. Their role involves coordinating and executing the technical aspects of production, such as lighting, sound, set design, costumes, and acting, using their skills and techniques to transform the theatrical text into a successful stage performance. The artistic mediator significantly impacts the quality of the theatrical work and creates a distinct viewing experience for the audience. Technological advancements and continuous updates in theater contribute to the development of the artistic mediator, expanding their capabilities in creative embodiment and artistic creation. This evolution leads to improved reception conditions and opens up new horizons for viewing and interacting with theatrical productions.